2016
DOI: 10.1161/circoutcomes.116.003067
|View full text |Cite
|
Sign up to set email alerts
|

Health Insurance Trajectories and Long-Term Survival After Heart Transplantation

Abstract: Background-Health insurance status at heart transplantation influences recipient survival, but implications of change in insurance for long-term outcomes are unclear. Methods and Results-Adults aged 18 to 64 receiving first-time orthotopic heart transplants between July 2006 and December 2013 were identified in the United Network for Organ Sharing registry. Patients surviving >1 year were categorized according to trajectory of insurance status (private compared with public) at wait listing, transplantation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 22 publications
(37 reference statements)
3
31
0
Order By: Relevance
“…The effect of a well deployed social security system with a compulsory health insurance coverage, providing full reimbursement of immunosuppressive and other drugs, has not been studied extensively in heart recipients (19)(20)(21)(22). It seems logical that these facilities, present in our country, decrease the risk of non-adherence and postponing medical help.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of a well deployed social security system with a compulsory health insurance coverage, providing full reimbursement of immunosuppressive and other drugs, has not been studied extensively in heart recipients (19)(20)(21)(22). It seems logical that these facilities, present in our country, decrease the risk of non-adherence and postponing medical help.…”
Section: Discussionmentioning
confidence: 99%
“…Until the end of 2015, 648 transplantations were performed in 615 patients, resulting in an average annual transplantation rate of 23 (range, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Thirty recipients received a second donor heart and one patient was transplanted three times.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Limitations in the work by Tumin et al 19 are present and are highlighted by recent work by these investigators. 18 Foraker et al, 18 in a recent analysis of the UNOS database, examined the influence of private or public health insurance coverage on 1-year and long-term survival after heart transplantation.…”
Section: Article See P 576mentioning
confidence: 92%
“…Addressing this issue, Tumin et al 19 examined the influence of health insurance trajectories or transitions on long-term survival after heart transplantation. The investigators examined data from the United Network for Organ Sharing (UNOS) registry and identified 10 298 first-time heart transplant recipients between the ages 18 and 64 years from July 2006 through December 2013.…”
Section: Article See P 576mentioning
confidence: 99%
See 1 more Smart Citation